Financing COVID-19 vaccination in sub-Saharan Africa: lessons from a nation-wide willingness to pay (WTP) survey in Ghana - Robert Kaba Alhassan; Edward Nketiah-Amponsah; Mustapha Immurana; Aaron Asibi Abuosi (BMC, 2022)
Abstract Background Over 13 million doses of the corona virus disease, 2019 (COVID-19) vaccines have been administered in Ghana as at March, 2022; 28.5% of the population have received one dose while 16.3% have been fully vaccinated. Cost associated with COVID-19 vaccinations in low- and middle-income countries (LMICs) requires rethinking on sustainable funding arrangements to consolidate gains made towards containing the COVID-19 pandemic. Objective Ascertain the determinants of willingness to pay (WTP) for COVID-19 vaccination among adult eligible population in Ghana, and prefer evidence-based policy recommendations on sustainable financing regime for COVID-19 vaccination in the global south. Methods Setting/design: A cross-sectional web-based survey was conducted among adult population aged 18 years and above across the sixteen (16) administrative regions of Ghana. Participants: A sub-sample of 697 participants willing to receive the COVID-19 vaccine was used as the unit of analysis. Outcome measures: main outcome measures of interests were willingness to pay for COVID-19 vaccination and the specific amount respondents were willing to pay. The odds of WTP and specific amount were predicted using the step-wise backward logistic regression and backward step-wise OLS, respectively. Results A total of 2,107 adult respondents aged 18 years and above were reached out to answer the questionnaire; 1,556 successfully completed the questionnaire, representing 74% response rate. Out of the 1,556 valid responses, 697 said they will receive the COVID-19 vaccine. Out of the 697 sub-sample willing to accept the vaccine, 386 (55%) were willing to pay an average of US$6.00 for the vaccine. Positive predictors of WTP were: being an educated male (OR = 0.55, 95% [CI = 0.366, 0.826], p = 0.004), married and educated (OR = 2.19, 95% [CI = 1.077, 4.445], p = 0.030), being a married health worker (OR = 0.43, 95% [CI = 0.217, 0.845], p = 0.015), and having positive perception of the vaccine (OR = 2.40, 95% [CI = 1.144, 5.054], p = 0.021). High WTP amounts correlated positively with adherence to COVID-19 prevention protocols (Coef. = 10.30, 95% [CI = 0.463, 20.137], p = 0.040) and being a health worker with tertiary education (Coef. = 56.339, 95% [CI = 8.524, 104.154], p = 0.021). Christians who are also health workers by occupation were less likely to pay higher amounts for the vaccine (Coef. = -71.431, 95% [CI = 118.821, -24.040], p = 0.003). Conclusions WTP for COVID-19 vaccination in Ghana is low relative to comparative studies in the sub-region. There is the need for accelerated, advocacy and public education on the benefits of vaccination. Likewise, there should be broader stakeholder engagement and national dialogue on sustainable financing options for COVID-19 vaccination as donor support continues to dwindle for LIMCs like Ghana.